Development of passive cooling with perforated plates and real-time monitoring for pv efficiency improvement - Sofijan, Armin; Sipahutar, Riman; Pradana, Wirawan Adi; Siregar, Baginda Oloan; Bizzy, Irwin; Sailah, Siti; Ardianto, Feby; Darma, Surya; Kamila, Ananda Putri; Dhafia, Vina Alya (Eastern-European Journal of Enterprise Technologies, 2025)
This study focuses on enhancing photovoltaic (PV) module performance through the development of a passive cooling method using perforated aluminum plates, supported by a real-time monitoring system. The core problem addressed is the thermal inefficiency of PV modules operating in hot, humid environments, where heat accumulation lowers energy output. A real-time data acquisition system was developed using Arduino to monitor voltage, current, surface temperature, humidity, and solar irradiance. Four identical polycrystalline PV modules were tested; three were equipped with aluminum plates of varying perforation diameters (10 mm, 12.5 mm, 15 mm), while one remained uncooled as a control. The results showed that the module with 15 mm perforations had the best performance, achieving a 61.04 W output under peak irradiance (1404 W/m2) and reducing surface temperature by nearly 10°C. These outcomes demonstrate that enhanced natural convection and evaporative effects, enabled by the larger perforations, significantly improved thermal regulation. The synchronized monitoring system validated the temperature-power relationship by capturing environmental dynamics in real time. Due to its energy independence, low cost, and simplicity, this integrated solution is particularly applicable in tropical regions or off-grid installations. The findings establish a practical basis for scalable deployment of passive cooling in PV systems, especially where active cooling is unfeasible